Fenomena Urban Heat Island dan kaitannya dengan urbanisasi wilayah di Subosukawonosraten - Shabrina Hasna Hayati; Paramita Rahayu; Erma Fitria Rini (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2026)
The Urban Heat Island (UHI) phenomenon has become an important challenge in urban areas as urbanization drives land-cover change and surface temperature rise. This study aimed to analyze the relationship of urbanization on Land Surface Temperature (LST) in Subosukowonosraten in 2000 and 2023 using a deductive quantitative approach based on Landsat 5 and Landsat 8 imagery processed through GIS. A macro-scale analysis was conducted to examine the relationship between land-cover change, vegetation density, and building density with LST, while a micro-scale analysis was used to identify hotspots, defined as areas experiencing significant temperature increases. The findings indicate a positive correlation between increasing building density and rising LST, as well as a negative correlation between decreasing vegetation density and rising LST. Areas classified as “hot” zones are predominantly composed of residential and industrial land (37%) and agricultural land (34%). This study concludes that urbanization in Subosukowonosraten contributes to the increase in LST and the intensification of UHI, highlighting the importance of more sustainable regional land-use planning and management strategies.